The law and practice of banking : volume 2: securities for bankers' Advances - Holden, J. Milnes (London : Pitman Publishing, 1993)
This eight edition of Volume 2 has been fully updated to include over six years change in banking practice and incorporates new statutes and leading reported cases. The text states clearly and concisely the law relating to the type of security under consideration and then describes the practice of the banking profession in the light of that law.
Includes index.
eej 20/08/2019
Loans
Keywords: Banking law; Banks and banking; Securities for bankers advances; Great Britain